The World Social Forum as a sub-political space for environmental justice: The case for South African grassroots empowerment within a network society - Leonard, Llewellyn (Journal of Social and Development Sciences, 2014)
The World Social Forum (WSF) has provided an international stage for civil society from across the globe to share ideas, strategies, tactics and struggles for creating â€˜another worldâ€™ against the failures of market inequalities. It attracts more than sixty thousand people pursuing the vision of ’Another World is Possible’, with the event becoming a symbol of hope for environmental, social and economic justice. How effective has the WSF been in projecting the concerns of the grassroots against inequalities produced? Should new strategies and tactics be forged amongst civil society so that this international platform becomes more meaningful for the marginalised? Through empirical work conducted at the 2011 WSF in Dakar, Senegal, supplemented with previous empirical work with civil society conducted in Durban, South Africa, this paper points to challenges that need to be addressed by civil society if â€˜another world is possible.â€™ Although there is an urgent need for local representative and civil society to mobilise social capital and include the grassroots into discussions in future WSF gatherings, the success of such an international platform is also influenced by historical, socio-economic and political contexts within countries influencing social capital within networks. Grassroots empowerment will help build more coherent actions that reflect the needs of those most affected by inequalities